Gamification in nursing teaching: assessment of the impact on learning (Research, Society and Development, 2021)
This study aims to identify the evidence available in the literature on the effectiveness of gamification as a teaching-learning strategy in nursing education. This is a scope review, developed according to the methodology of the Joanna Briggs Institute. The Cochrane, PubMed, Lilacs, Science Direct and ERIC databases were used. The search strategy was adjusted according to the protocols of each database and the descriptors for combinations were defined from the controlled vocabulary of the Medical Subject Headings (MeSH). Documents published in the last five years were used, with a final sample of 16 articles. It observed the predominance of the application of gamification online, having two studies that brought the use of games in person. All studies pointed out as positive the use of gamification in the classroom. It also shows that it can be understood as an additional resource in the teacher's work, bringing significant learning and a safe environment. There is a scarcity of studies related to the effectiveness of gamification in nursing education, but one can observe the extreme importance of inserting games as a teaching and learning strategy, as they help the student body in their intellectual and personal development.